2018
DOI: 10.1371/journal.pone.0202968
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of rural women's desired fertility: A survey in rural Shaanxi, China

Abstract: There has been evidence demonstrating that China has had a persistently low and below-replacement level fertility since early 1990s, causing concerns of a rapidly aging population and sustainability of the Chinese economy. To avoid adverse effects of excessively low fertility, the Chinese government has recently changed its family planning policy from "one-child policy" to "two-child policy." Nonetheless, the effectiveness of the newly initiated two-child policy is questionable if women's average desired numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
(73 reference statements)
1
25
0
1
Order By: Relevance
“…At the stage of UTCP, the SRB of rural women has declined to normal level, which is same as that of the urban women. The average lifetime desired birth for the rural women of childbearing age was about 1.71, below the total birth rate at the replacement level [28]. Women's marriage age, the pecuniary costs of having children, and social security benefits available for rural residents at retirement age, were significantly and negatively related to the willingness of giving birth.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…At the stage of UTCP, the SRB of rural women has declined to normal level, which is same as that of the urban women. The average lifetime desired birth for the rural women of childbearing age was about 1.71, below the total birth rate at the replacement level [28]. Women's marriage age, the pecuniary costs of having children, and social security benefits available for rural residents at retirement age, were significantly and negatively related to the willingness of giving birth.…”
Section: Discussionmentioning
confidence: 89%
“…numerous negative consequences and had significant impact on childbearing decisions [20,27]. Evidence shows that China has entered an era of low birth rate [28], any restriction policies on birth may no longer be necessary. In fact, after the Two-Child Policy, the birth rate did not increase sharply.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that people with college or higher education showed a lower propensity to have induced abortions, but their pregnancies were more likely to be aborted. Higher-educated people were more likely to use effective contraception to reduce the risk of unwanted pregnancy, but they also demonstrated less of a desire to have children [15].…”
Section: Discussionmentioning
confidence: 99%
“…Fertility intent is regarded as a predictor of fertility behaviour;5 and in addition to policy, intent to procreate is also influenced by individual, social, economic and cultural factors 4 6. Several investigators have reported on the intent to have a second child in China (which varies from 13.2% to 69.3%) and its associated factors, including age, occupation, educational level, and gender of the first child 4–8. However, these studies were principally conducted in particular populations or settings, such as a rural population, women attending outpatient gynaecology clinics, or women from one specific province.…”
Section: Introductionmentioning
confidence: 99%